Avaliação do efeito probiótico de Lactobacillus rhamnosus EM1107 adicionado em queijo de coalho caprino em ratos com salmonelose - Rolim, Fernanda Rodrigues Leite (2019)
Probiotics are microorganisms that promote host health benefits when consumed in adequate amounts. The food is a vehicle that protects the strains during the passage through the gastrointestinal tract, and the cheeses have advantages such as: availability of nutrients, high pH, higher buffering capacity and low oxygen content. The application of probiotics in cheese has expanded and, therefore, this thesis aimed to produce a review article on the general concepts of probiotics and on researches that used different probiotic strains in various types of cheese, as well as the evaluations. in vitro or in vivo used in these studies; and an original article that aimed to evaluate the probiotic effect of Lactobacillus rhamnosus EM1107, added or not in goat curd cheese, in rats infected with Salmonella enterica by evaluating the oxidative excess marker profile, immune system modulation and intestinal microbiota. Male 6-week-old albino Wistar rats were selected and randomly assigned to five experimental treatments: negative control group (NC): rats that received saline and were not infected with salmonellosis; positive control group (PtC): animals that received saline and were infected with salmonellosis; control goat cheese group (CCh): animals treated with cheese without probiotic culture and infected with salmonellosis; L. rhamnosus EM1107 (LrCh) goat cheese group added: animals treated with probiotic cheese and infected with salmonellosis and L. rhamnosus group (EM1107): rats that were treated with the probiotic inoculum and were infected with salmonellosis. According to the results, administration of EM1107, either in a cheese matrix or isolated, was able to reduce Salmonella colonization on the first day after infection in the intestinal lumen. Metataxonomic analysis of the 16S rRNA gene revealed that the probiotic led to significant changes in the intestinal microbiota of rats by modulation of commensal bacteria, such as those belonging to the Lachnospiraceae family and genera Blautia, Prevotella and Lactobacillus. The immunomodulatory parameters of NF-κB, TNF-α, IL-1β and IFN-γ were also reduced on different days of infection, but EM1107, when administered alone, had better influence of these parameters, besides the reduction in MPO and MDA levels. In the histopathological analysis, a reduction in intestinal tissue inflammation was observed in rats of the EM1107, LrCh and CCh groups compared to the PtC group. Thus, it can be concluded that EM1107, alone or added to cheese, was able to minimize Salmonella-induced tissue damage by modulating intestinal microbiota, immunological parameters and reducing intestinal inflammation at histopathological level of rats. LrCh and EM1107 groups, with emphasis on the latter group, which had better effects associated with antioxidant and immunomodulatory properties than probiotic cheese, although cheese added or not with probiotic strain could mitigate damage to intestinal tissue.